Analysis of donors trust and relationship commitment in lembaga amil zakat in Indonesia - Tanti Handriana (Journal of Economics, Business, and Accountancy Ventura, 2016)
The purpose of this study is to investigate the role of donors trust and relationship commitment in a non-profit organization. This study used a survey method and takes individual donors of Lembaga Amil Zakat as the research samples. There are 117 respondents used in this research. Structural Equation Modeling (SEM) is selected as the analysis technique. The findings of the study reveal that (1) shared values have significant effect on trust; (2) relationship marketing investment has significant effect on trust; (3) trust has significant effect on relationship commitment; and (4) trust has significant effect on future intentions. The contribution of this study is mainly to broaden the application of social exchange theory and relationship marketing concept which are suitable not only for profit-oriented organizations, but also for nonprofit oriented organizations.